The Effect Of Economic Value Added And Financial Ratio On Sharia Stock Return - Ahmad Andy Adinegara; Anita Dwi Utami; Shofia Annisa Ratnasari; Syafira Mariana; Tiana Fenny Krisdina (IAEI, 2023)
This research investigates the impact of economic volatility on the market capitalization of the Jakarta Islamic Index(JII) from 2019 to 2021. Analysis of stock prices and returns for companies in this index reveals fluctuations that are correlated with economic disruption. In addition, research explores the significance of financial ratios, especially Return On Assets (ROA), as an important tool for assessing company performance. Economic Value Added (EVA) was also tested as a factor influencing stock returns, producing different results from previous research. Thirteen companies in the JII were the research samples, selected through purposive sampling based on criteria such as consistent registration for three years, annual financial reports for the 2019-2021 period, and not using foreign currency. Data obtained from company reports. This research uses an explanatory quantitative approach, by applying panel data regression and models such as Common Effect, Fixed Effect, and Random Effect. The results of statistical analysis for the EVA variable show that there is no significant influence on the returns of sharia shares listed on the JII. Meanwhile, the ROA variable shows that ROA has a significant effect on stock returns in companies listed on the JII.